Problématique De L’usage Des Contraceptifs Hormonaux En Milieu Rural Gwa De Domlon (Côte d’Ivoire) - Judicaël, Anoua Adou Serge (European Scientific Journal, ESJ, 2016)
The use of hormonal contraceptives still remain a problem in rural areas. This situation is due to the social value of childbearing, the lack of correct information and the natural control of contraception among the Gwa rural community of Domlon. These difficulties reveal the lack of affection for mothers who are significantly exposed to the dangers of high childbearing. In Domlon sanitary environment, this risky childbearing attitude seems a serious problem that requires sensitizational and educational actions concerning the use of modern contraceptives for a less risky childbearing.